2006
DOI: 10.1152/ajpcell.00534.2005
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Ca2+-desensitizing mechanisms activated by forskolin and phenylephrine pretreatment, but not 8-bromo-cGMP

Abstract: Contractile stimuli can sensitize myosin to Ca2+ by activating RhoA kinase (ROK) and PKC that inhibit myosin light chain phosphatase (MLCP) activity. Relaxant stimuli, acting through PKA and PKG (cyclic nucleotide-dependent protein kinases), and pretreatment with contractile agents such as phenylephrine (PE), can desensitize myosin to Ca2+. It is unknown precisely how these stimuli cause Ca2+ desensitization. To test the hypothesis that PKA, PKG, and PE pretreatment signaling systems converge to cause relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 56 publications
5
28
2
Order By: Relevance
“…These results indicate that cAMP/PKA is involved in the response to G-1, and the result that G-1 increased PKA activity in porcine coronary artery SMCs further confirmed this notion. Consistent with our results, it was reported previously that forskolin and db-cAMP, a PKA activator, inhibited a KClinduced increase in MYPT-1 phosphorylation at Thr 853 and the phosphorylation of MLC, thus relaxing femoral arteries from adult New Zealand white rabbits (56). Taken together, these findings suggest that through cAMP/PKA signaling, G-1 induced activation of MLCP, which resulted in dephosphorylation of MLC in coronary artery SMCs.…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that cAMP/PKA is involved in the response to G-1, and the result that G-1 increased PKA activity in porcine coronary artery SMCs further confirmed this notion. Consistent with our results, it was reported previously that forskolin and db-cAMP, a PKA activator, inhibited a KClinduced increase in MYPT-1 phosphorylation at Thr 853 and the phosphorylation of MLC, thus relaxing femoral arteries from adult New Zealand white rabbits (56). Taken together, these findings suggest that through cAMP/PKA signaling, G-1 induced activation of MLCP, which resulted in dephosphorylation of MLC in coronary artery SMCs.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, and depending on vascular beds, the endothelial NO pathway has been found to be involved in the relaxation elicited by activation of ␤ARs (8, 28). The final transduction mechanisms of these pathways involve several processes, including membrane hyperpolarization due to opening of K ϩ channels, (34), enhanced Ca 2ϩ sequestration by the endoplasmic reticulum (33), or reduction in Ca 2ϩ sensitization (35). When the femoral arteries were stimulated by high K ϩ (62.5 mM), opening of K ϩ channels could not cause further hyperpolarization and thus could not exert any further relaxation effect (40).…”
Section: Discussionmentioning
confidence: 99%
“…For example, high K + induces less contractile tension for a given increase in [Ca 2+ ]i than agonists, such as norepinephrine in ferret portal veins, norepinephrine, prostaglsndins, and endothelin-1 in rat aortas, thromboxane analogues and phenylephrine in rabbit pulmonary arteries, carbachol in canine tracheas, and pilocarpine in ileum (Karaki, 1989). Furthermore, several reports have suggested that receptor-agonists induce greater myosin light chain phosphorylation than high K + at a given [Ca 2+ ]i (Ratz, 1999;Porter et al, 2006). A decrease in Ca 2+ sensitivity due to cAMP has also been reported (Rembold and Chen, 1998;Rembold et al, 2001).…”
Section: Introductionmentioning
confidence: 92%
“…It is generally accepted that adenosine 3',5'-cyclic monophosphate (cAMP) is the intracellular messenger by which many smooth muscle relaxants inhibit the generation or maintenance of muscle tension (Murray, 1990;Lincoln and Cornwell, 1991;Ozaki et al, 1992;Murthy, 2006;Porter et al, 2006). Smooth muscle relaxation induced by cAMP occurs after activation of cAMP-dependent protein kinase (Eckly-Michel et al, 1997;Porter et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation